Impact of ethnicity on the outcome of men with metastatic, hormone‐sensitive prostate cancer. Issue 9 (5th January 2017) - Bernard, Brandon; Muralidhar, Vinayak; Chen, Yu‐Hui; Sridhar, Srikala S.; Mitchell, Edith P.; Pettaway, Curtis A.; Carducci, Michael A.; Nguyen, Paul L.; Sweeney, Christopher J.
Abstract : BACKGROUND: Prostate cancer (PCa) outcomes are impacted by socioeconomic and biologic factors. Ethnicity plays a role in the former, but little is known about the responsiveness of metastatic PCa to androgen‐deprivation therapy (ADT) among races. METHODS: The Surveillance, Epidemiology, and End Results (SEER) registry was used to identify men who were diagnosed with distant, de novo, metastatic PCa from 2004 to 2012. Patterns of presentation, overall survival (OS), and PCa‐specific mortality (PCSM) were determined for each race. E3805 clinical trial data also were retrospectively reviewed to assess outcomes of ADT and ADT plus docetaxel by race. RESULTS: Of all PCa diagnoses in SEER, distant, de novo, metastatic disease was diagnosed in 4.2% of non‐Hispanic whites, 5.8% of Hispanic whites, 5.7% of blacks, 5.5% of Asians/Pacific Islanders, and 8.8% of American Indians/Alaska Natives ( P  < .001; chi‐square test). The median OS differed by race, with superior OS observed among Asian men (30 months) than among men of other races (range, 24‐25 months; P  < .001). Asians also had a superior median PCSM (54 months) compared with the other races (range, 35‐40 months; P  < .001). In E3805, chemohormonal therapy was associated with a median OS of 58.1 months (95% confidence interval, 48.8‐72.9 months) and 57.6 months (95% confidence interval, 27.7‐57.6 months) in non‐Hispanic whites and blacks, respectively. Few Asians participated in the E3805 trial. CONCLUSIONS: Asian men have superior median OS and PCSM for distant, de novo, metastatic PCa than men of other race. Non‐Hispanic whites and blacks who receive treatment with ADT or chemohormonal therapy have comparable outcomes. Cancer 2017;123:1536–1544. © 2017 American Cancer Society . Abstract : Among patients diagnosed with distant, de novo, metastatic prostate cancer, Asian men have a superior outcome compared with men of other races. Furthermore, black men and non‐Hispanic white men have comparable outcomes when they receive treatment with androgen‐deprivation therapy or chemohormonal therapy.